“Factores determinantes en la producción de los pequeños productores de banano del cantón la Maná, 2022”. - Bermello Angulo, Karen Daira (2022)
The present research work under the topic, "DETERMINING FACTORS IN THE PRODUCTION OF SMALL-SCALE BANANA PRODUCERS IN THE CANTON LA MANÁ 2022", had as a general objective to establish the main determining factors in the production of small-scale banana growers. This study conducted a documentary, bibliographic, and descriptive design as a type of research to search for information of great relevance to the subject of study for generating the theoretical framework through the use of books, internet sources, magazines, and scientific articles. On the other hand, the field research allowed the researchers to employ information collecting methods such as an interview that was carried out with the micro-entrepreneurs in bananas production of the canton by collecting data at first-hand about the factors that determine banana production and how they affect the small producers of the canton. The main results showed that the factors involved in the production process include land, capital, labor, market, supply or demand, and international prices. To conclude, the main determining factors that influence the banana production of small producers are labor, with a medium-high impact, the inputs used in production with a high repercussion, financing access with a very high impact, the availability of economic resources, as well as technology that displays a high potential impact. The project's effect at the socioeconomic level is positive due to the generation of good economic income for the families that work in the banana plantations. It also contributes to economic improvement by generating job opportunities. Based on this, it was possible to recommend this proposal implementation for mitigating the effect of the factors involved in the production. In such a manner, strategies implementation can be convenient to increase product quality, sales, mass-produce, and greater profitability.